Comparative Study of Entrepreneurial Orientation and Financial Management Strategies in Women MSMEs - Retno Endah Supeni; Maheni Ika Sari (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study aims to analyze in depth the influence of entrepreneurial orientation, consisting of dimensions of innovation, risk taking, and proactive attitude, on decision making in financial management and its impact on financial performance in women-owned MSMEs from three ethnic groups, namely Javanese, Madurese, and Osing, spread across East Java. This study also aims to compare the differences in influence between the three ethnic groups. The research method used is a quantitative approach with the Structural Equation Modeling (SEM) analysis tool processed using AMOS software, on a sample of between 100 and 200 female MSME actors selected purposively, with a minimum provision of 30 respondents from each ethnic group. In this study, entrepreneurial orientation is set as the independent variable, financial management decision making as the mediator variable, and financial performance as the dependent variable. The results of the study indicate that innovation and risk taking have a significant positive effect on financial decisions, but have a negative impact on financial performance, while proactiveness is not significant. Financial management decisions are proven to significantly improve the financial performance of MSMEs.